A constrained optimisation approach for designing reliable robust H∞ control systems - Sim, Hua Heng Allan (Curtin University, 2016)
This research addresses passive fault-tolerant control problems for linear uncertain systems via reliable state feedback and output feedback robust H∞ controllers. Structured uncertainties considered are required to satisfy integral quadratic constraints. These controllers are to obtain an absolutely stable closed-loop system with a specified disturbance attenuation level. Solutions to these control problems involve solving parameterised Riccati equation(s). A feasible set of parameters used to solve the Riccati equation(s) is computed using a differential evolution algorithm.